Radioactive Investigation of Sunflower Seeds - Potrous, Saad M (Science and Technology - Recent Updates and Future Prospects Vol. 3, 2024)
The effects of the topic of the scientific news published by using Sunflower oil which is present in every home that may cause dangerous diseases on continuous consumption and that may be a cause of development of liver diseases, including cirrhosis and cancer. I would like to state that scientific research and studies on the Sunflower plant indicate that its roots absorb radioactive Uranium particles in the soil and are transferred to the stem and leaves and then to the flowers of the plant from which vegetable oils are extracted. In this work, a radioactive examination was conducted on a sample of Sunflower seeds and their seed powder taken from an unknown source soil, using a device for nuclear particles examination type Inspector EXP American-made. The test results showed that the seeds have a radioactivity measurement value of (0.008 mR/hr) and the seed powder has a value of (0.015 mR/hr), which falls within the natural radiation background of (10 mR/hr), which does not have any negative impact on human health. These results confirm that the Sunflower plant was grown in soil free of radioactive Uranium. Therefore, the manufacturers and producers of Sunflower plant oils must examine the soil of the fields for growing the Sunflower plants and ensure that it is free of radioactive Uranium, and thus the seeds are free of any radioactive activity that leads to harm to human health. By consuming vegetable oils in cooking food.